Exploring the role of co-production in enhancing happiness and well-being in the UAE - ALYAMMAHI, ABDULLA JUMAH (2023)
The aim of this research is to discover the views, practices and advice of experienced employees and citizens on how co-production can enhance happiness and well-being. The global challenges led governments all over the world to believe in the role of co-production in providing effective public services for citizens to increase their happiness and well-being. However, the literature of co-production as a factor for happiness and well-being has not been given much attention and remains limited or confined to certain factors such as wealth, health, and employment. The study applied a qualitative method utilising semi-structured interviews with 35 participants. The sample was divided into two groups. The first group consisted of the employees from the Ministry of Interior (MOI) who already managed some co-production practices. The second group was the citizens who have already experienced the co-production process with the (MOI). The data analysis was accomplished using Nvivo. The research found that there is a strong belief in the role of co-production in enhancing the levels of happiness and well-being. In addition, the findings revealed that there is a need for a comprehensive strategy for co-production with a set of skills that co-producers should have. The thesis also sheds light on the benefits of co-production, such as enhancing innovation and maintaining sustainability. Moreover, the thesis identified some challenges and barriers that can limit co-production. This thesis can contribute to knowledge by presenting a conceptual framework for co-production and suggest a practical set of required skills of co-production to be considered by public organizations.